Neuralink and dementia - Faatimah Patel (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Brain-computer interfaces (BCIs) came into development in the late 1960s and early 1970s. Over the decades, as technology has progressed, humanity has quickly reached the point where these devices that are generally seen as dangerous can now be implanted in a human brain to be tested and trialled. BCIs come in many forms to aid people with debilitating conditions and disabilities to communicate, move, and perhaps even improve memory. One such device is the ‘Link’ produced by Neuralink. Currently, the device is being trialled on two patients that are quadriplegic, to help them move and regain their autonomy. Eventually, it is hoped that patients with illnesses such as dementia will be trialled and tested; however, there are concerns related to the invasive nature of the device. The general public are worried about what the companies who implant the devices may do with the data, as well as how accessible and affordable it will be.